Solution Structure and NMR Chemical Shift Perturbations of the Arabidopsis BCCP1 Identify Intersubunit Interactions Potentially Involved in the Assembly of the Heteromeric Acetyl‐CoA Carboxylase - Kiran‐Kumar Shivaiah; Ganesh P. Subedi; Adam W. Barb; Basil J. Nikolau (Plant Direct)
ABSTRACT Biotin carboxyl carrier protein (BCCP) is a subunit of the heteromeric acetyl‐CoA carboxylase (htACCase), and it chemically links the two half‐reactions that constitute the formation of malonyl‐CoA from acetyl‐CoA, a critical reaction in fatty acid biosynthesis. Because plants are a major source of edible fats and oils, it is important to understand the structural organization of the plant htACCase, relative to its potential to regulate fatty acid biosynthesis in plant plastids. Moreover, unique to the plant htACCase, noncatalytic subunits called biotin attachment domain–containing (BADC) proteins are important in the assembly of the holoenzyme, and they specifically interact with the BCCP and the biotin carboxylase (BC) subunits. We report herein NMR structural studies of the Arabidopsis BCCP isozymes (BCCP1 and BCCP2). We calculated the structure of C‐terminal domain of BCCP1 (K200‐P280) and explored structural changes in the BCCP1 protein upon its interactions with BC and BADC. The chemical shift perturbation experiments identified potential surface residues on the BCCP1 protein that may facilitate physical interactions between BC and BADC proteins. These studies indicate that the BADC protein interacts with a “thumb”‐like protrusion, which is a common structural feature of the bacterial and plant BCCPs, and thereby acts as a potential “cap” to facilitate the assembly of a BC–BCCP–BADC complex.